A modular approach to inorganic phosphazane macrocycles - Plajer, Alex; García-Rodríguez, Raúl; Benson, Callum G. M.; Matthews, Peter D.; Bond, Andrew D.; Singh, Sanjay; Gade, Lutz H.; Wright, Dominic S. (Angewandte Chemie, 2017)
Inorganic macrocycles, based on non-carbon backbones, present exciting synthetic challenges in the systematic assembly of inorganic molecules, as well as new avenues in host-guest and supramolecular chemistry. Here we demonstrate a new high-yielding modular approach to a broad range of trimeric and hexameric S- and Se-bridged inorganic macrocycles based on cyclophosphazane frameworks, using the building blocks [S=(H)P(μ-NR)]2. The method involves the in situ generation of the key intermediate [E (S )P(μ-NR)]22−(E=S, Se) dianion, which can be reacted with electrophilic [ClP(μ-NR)]2 to give PIII/PV hexameric rings or reacted with I2 to give trimeric PV variants. Important issues which are highlighted in this work are the competitive bridging ability of S versus Se in these systems and the synthesis of the first air-stable and chiral inorganic macrocycles.